Composite lithium manganese iron phosphate material as well as preparation method and application thereof

By adjusting the distribution of manganese elements in the composite lithium manganese ferrophosphate material and adopting a cladding structure, the manganese dissolution is suppressed by ion exchange reaction, which solves the problem of manganese ion dissolution and improves the cycling performance and capacity of the battery.

CN119725437APending Publication Date: 2025-03-28湖北金泉新材料有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411826194.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Lithium manganese iron phosphate is easily corroded by acidic substances generated by electrolyte decomposition in lithium-ion batteries, resulting in the dissolution of manganese ions, reducing battery capacity, and affecting cycle life and stability.

Method used

By adjusting the distribution of manganese elements in the composite lithium manganese ferrophosphate material, the structural design of the core, the first cladding layer and the second cladding layer are adopted, and the ion exchange reaction in the iron-containing solution is used to inhibit the dissolution of manganese elements.

Benefits of technology

It significantly improves the structural stability of composite lithium manganese iron phosphate material, extends the cycle life of the battery, and improves its capacity and circulation performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005185001870000031
    Figure BDA0005185001870000031
Patent Text Reader

Abstract

The invention provides a composite lithium manganese iron phosphate material as well as a preparation method and application thereof. The composite lithium manganese iron phosphate material sequentially comprises an inner core, a first coating layer and a second coating layer from inside to outside, wherein the inner core comprises a first metal material, the molecular formula of the first metal material is LiMnxFe (1-x) PO4, and x is more than or equal to 0.4 and less than or equal to 0.6; the first coating layer comprises a second metal material, and the molecular formula of the second metal material is LiMnyFe (1-y) PO4, 0 < = y < lt >; 0.4 part; the second coating layer includes a carbon material. By adjusting the distribution of the manganese element in the composite lithium manganese iron phosphate material, the manganese element on the surface of the lithium manganese iron phosphate is inhibited from being dissolved out of a negative electrode through an electrolyte, so that the structural stability of the composite lithium manganese iron phosphate material is improved, and the cycle performance and the capacity of the composite lithium manganese iron phosphate material are further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion battery materials, and in particular relates to a composite lithium manganese iron phosphate material and a preparation method and application thereof. Background Art

[0002] Lithium manganese iron phosphate (LMFP) is a new type of lithium-ion battery cathode material that combines the advantages of lithium iron phosphate (LFP) and lithium manganese phosphate (LMP). Compared with traditional lithium iron phosphate, lithium manganese iron phosphate has improved energy density, low temperature performance and safety; compared with ternary materials, lithium manganese iron phosphate has lower cost, higher safety and environmental friendliness.

[0003] However, lithium iron manganese phosphate still has some defects. Specifically, the acidic substances produced by the decomposition of the electrolyte in the lithium-ion battery may corrode the manganese ions in the lithium iron manganese phosphate, accelerate the disproportionation reaction of manganese, and cause the manganese ions to dissolve from the lithium iron manganese phosphate. This manganese dissolution not only reduces the capacity of the lithium-ion battery, but also may damage the solid electrolyte interface (SEI) film of the negative electrode, affecting the cycle life and stability of the battery.

[0004] In order to overcome the manganese dissolution problem of lithium manganese iron phosphate, researchers are exploring various modification technologies, such as nano-sizing, metal ion doping and other methods, to improve the electrochemical performance and commercialization potential of lithium manganese iron phosphate batteries. However, the above modification methods still have some shortcomings. For example, although nano-sizing can shorten the diffusion path of lithium ions, if the nanoparticles are not prepared and processed properly, additional defects or stresses may be introduced, which will aggravate the problem of manganese dissolution. Similarly, the method of metal ion doping may change the original crystal structure of lithium manganese iron phosphate due to the doping elements, especially the radius of the doping elements is quite different from the elements in lithium manganese iron phosphate, which may cause lattice distortion, affect the structural stability of lithium manganese iron phosphate and aggravate the problem of manganese dissolution. Therefore, whether it is the nano-sizing modification method or the metal ion doping modification method, the repetition rate is low, and it is difficult to produce the same product in industrial applications. Summary of the invention

[0005] In order to improve the manganese dissolution problem of lithium manganese iron phosphate, the present application provides a composite lithium manganese iron phosphate material and a preparation method and application thereof.

[0006] According to one aspect of the present application, a composite lithium iron manganese phosphate material is provided, wherein the composite lithium iron manganese phosphate material is arranged from the inside to the outside in sequence including a core, a first coating layer and a second coating layer; wherein the core includes a first metal material, and the molecular formula of the first metal material is LiMn x Fe (1-x) PO4, 0.4≤x≤0.6; the first coating layer includes a second metal material, the molecular formula of the second metal material is LiMny Fe (1-y) PO4, 0≤y<0.4; the second coating layer includes a carbon material. The present application adjusts the distribution of manganese elements in the composite manganese iron phosphate lithium material to inhibit the manganese elements on the surface of the manganese iron phosphate from being dissolved from the negative electrode through the electrolyte, thereby improving the structural stability of the composite manganese iron phosphate lithium material, and further improving its cycle performance and capacity.

[0007] Preferably, the median particle size of the composite lithium manganese iron phosphate material is 6-10 μm, and the thickness of the first coating layer is 1-5 nm.

[0008] Preferably, the thickness of the second coating layer is 2-5 nm.

[0009] The second aspect of the present application provides a method for preparing the composite manganese iron phosphate lithium material as described above, the method comprising the following steps: S1. Mixing the manganese iron phosphate precursor with a lithium source, a carbon source, and a solvent to obtain a first slurry; S2. Then grinding the first slurry to obtain a second slurry; S3. Mixing the second slurry with an iron-containing solvent, reacting at 20 to 80°C for 2 to 12 hours to obtain a third slurry; S4. After the third slurry is dried, the obtained powder is calcined under the protection of an inert gas to obtain a composite manganese iron phosphate lithium material. Since the ionic radius of iron ions and manganese ions is relatively close, the present application cleverly uses an iron-containing solution to replace the manganese ions on the surface of the manganese iron phosphate precursor through an ion exchange reaction, which can effectively alleviate the manganese dissolution problem and thereby improve its cycle performance and capacity.

[0010] Preferably, the iron-containing solution includes at least one of a soluble organic iron salt and a soluble inorganic iron salt; wherein the soluble organic iron salt includes ferric acetate, ferric oxalate, and ferric ferrocyanide; and the soluble inorganic iron salt includes at least one of ferric sulfate, ferrous sulfate, ferric chloride, and ferrous nitrate.

[0011] Preferably, the iron-containing solution includes a soluble organic iron salt and a soluble inorganic iron salt, and the mass ratio of the soluble organic iron salt to the soluble inorganic iron salt is 6 to 9:1 to 4. The present application can effectively accelerate the ion exchange reaction by simultaneously introducing a soluble organic iron salt and a soluble inorganic iron salt into the iron-containing solution, and introduce an organic carbon source to further significantly improve the manganese dissolution problem of lithium manganese iron phosphate, thereby improving its cycle performance.

[0012] Preferably, in the iron-containing solution, the mass concentration of iron ions is 20-60%; and the mass of the iron-containing solution added is 0.5-10% of the ferromanganese phosphate precursor in the second slurry.

[0013] Preferably, in S1, calculated by mass ratio, the ratio of ferromanganese phosphate precursor: lithium source: carbon source is 1: 0.2-0.25: 0.03-0.1.

[0014] Preferably, in S1, the mixing time of the ferromanganese phosphate precursor, the lithium source, the carbon source and the solvent is 1 to 2 hours.

[0015] Preferably, the particle size of the second slurry is 0.3-0.8 μm.

[0016] Preferably, in S2, the grinding process includes any one of ball milling and fine milling.

[0017] Preferably, in S4, the drying process is a spray drying process.

[0018] Preferably, in S4, the reaction temperature of the calcination treatment is 400 to 800° C., and the reaction time is 1 to 10 hours.

[0019] According to a third aspect of the present application, a lithium-ion battery is provided. The lithium-ion battery comprises the composite lithium iron manganese phosphate material as described above or the composite lithium iron manganese phosphate material prepared by the method for preparing the composite lithium iron manganese phosphate material as described above. DETAILED DESCRIPTION

[0020] In order to enable those skilled in the art to better understand the technical solutions in this application, the technical solutions in this application will be clearly and completely described below in conjunction with the embodiments of this application. Obviously, the described embodiments are only part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of this application.

[0021] Example 1

[0022] 1. Raw materials required for the preparation of composite manganese iron phosphate lithium materials

[0023] The raw materials required for preparing the composite lithium iron manganese phosphate material in this embodiment are shown in Table 1.

[0024]

[0025] 2. Method for preparing composite lithium manganese iron phosphate material

[0026] S1. mixing a ferromanganese phosphate precursor with a lithium source, a carbon source, and a solvent to obtain a first slurry;

[0027] S2. The first slurry is then subjected to ball milling and fine grinding to obtain a second slurry having a particle size of 0.5 μm;

[0028] S3. The second slurry is mixed with an iron-containing solvent and reacted at 50° C. for 6 hours to obtain a third slurry, wherein the mass concentration of iron ions in the iron-containing solution is 15%; and the mass of the iron-containing solution added is 0.002% of the ferromanganese phosphate precursor in the second slurry;

[0029] S4. After the third slurry is spray-dried, the obtained powder is calcined under the protection of an inert gas, wherein the reaction temperature of the calcination treatment is 600° C. and the reaction time is 5 hours to obtain a composite manganese iron lithium phosphate material.

[0030] 3. Preparation of Lithium-ion Batteries

[0031] The composite lithium manganese iron phosphate material prepared above is mixed with the conductive agent acetylene black and the binder PVDF in a mass ratio of 9:0.2:0.8, and a certain amount of organic solvent NMP is added, and then coated on aluminum foil after stirring to make a positive electrode. The negative electrode uses a metal lithium sheet, and the diaphragm is a Celgard2400 polypropylene porous membrane; the solvent in the electrolyte is a solution composed of EC, DMC and EMC in a mass ratio of 1:1:1, the solute is LiPF6, and the concentration of LiPF6 is 1.0 mol / L. The positive electrode sheet, negative electrode sheet, diaphragm, and electrolyte prepared above are assembled into a 2023 button battery in a glove box.

[0032] Example 2

[0033] This embodiment prepares a composite manganese iron lithium phosphate material and a lithium ion battery with reference to the formula and method provided in Example 1. The difference from Example 1 is that when preparing the composite manganese iron lithium phosphate material, this embodiment uses a mass ratio of organic iron salt ferric acetate: inorganic iron salt ferric chloride of 6:4. Except for the above difference, the operating steps for preparing the composite manganese iron lithium phosphate material and the lithium ion battery in this embodiment are strictly consistent with those in Example 1.

[0034] Example 3

[0035] This embodiment prepares a composite manganese iron lithium phosphate material and a lithium ion battery with reference to the formula and method provided in Example 1. The difference from Example 1 is that when preparing the composite manganese iron lithium phosphate material, this embodiment uses a mass ratio of organic iron salt ferric oxalate: inorganic iron salt ferrous sulfate of 3:7. Except for the above difference, the operating steps for preparing the composite manganese iron lithium phosphate material and the lithium ion battery in this embodiment are strictly consistent with those in Example 1.

[0036] Example 4

[0037] This embodiment prepares composite lithium iron manganese phosphate material and lithium ion battery with reference to the formula and method provided in Example 1. The difference from Example 1 is that when preparing the composite lithium iron manganese phosphate material, this embodiment uses an equal mass fraction of organic iron salt ferrous lactate to replace ferric nitrate. Except for the above difference, the operating steps for preparing the composite lithium iron manganese phosphate material and lithium ion battery in this embodiment are strictly consistent with those in Example 1.

[0038] Example 5

[0039] This embodiment prepares a composite lithium iron manganese phosphate material and a lithium ion battery with reference to the formula and method provided in Example 1. The difference from Example 1 is that when preparing the composite lithium iron manganese phosphate material, this embodiment uses an equal mass fraction of iron sulfate instead of iron succinate. Apart from the above differences, the operating steps for preparing the composite lithium iron manganese phosphate material and the lithium ion battery in this embodiment are strictly consistent with those in Example 1.

[0040] Example 6

[0041] This example prepares a composite lithium iron manganese phosphate material and a lithium ion battery with reference to the formula and method provided in Example 1. The difference from Example 1 is that when preparing the composite lithium iron manganese phosphate material, this example replaces the carbon source PEG with an equal mass fraction of water. Except for the above differences, the operating steps for preparing the composite lithium iron manganese phosphate material and the lithium ion battery in this example are strictly consistent with those in Example 1.

[0042] Example 7

[0043] This embodiment prepares composite manganese iron lithium phosphate material and lithium ion battery with reference to the formula and method provided in Example 1. The difference from Example 1 is that when preparing the composite manganese iron lithium phosphate material, this embodiment uses an equal mass fraction of organic iron salt ferrous fumarate to replace organic iron salt ferrous lactate. Except for the above difference, the operating steps for preparing the composite manganese iron lithium phosphate material and lithium ion battery in this embodiment are strictly consistent with those in Example 1.

[0044] Example 8

[0045] This embodiment prepares composite manganese iron lithium phosphate material and lithium ion battery with reference to the formula and method provided in Example 1. The difference from Example 1 is that when preparing the composite manganese iron lithium phosphate material, this embodiment uses ferric chloride in equal parts by mass to replace inorganic iron salt ferrous sulfate. Except for the above differences, the operating steps for preparing the composite manganese iron lithium phosphate material and lithium ion battery in this embodiment are strictly consistent with those in Example 1.

[0046] Example 9

[0047] This embodiment prepares a composite manganese iron lithium phosphate material and a lithium ion battery with reference to the formula and method provided in Example 1. The difference from Example 1 is that when preparing the composite manganese iron lithium phosphate material, this embodiment adjusts the water content in the iron-containing solution so that the mass concentration of iron ions in the iron-containing solution is 20%. Except for the above differences, the operating steps for preparing the composite manganese iron lithium phosphate material and the lithium ion battery in this embodiment are strictly consistent with those in Example 1.

[0048] Example 10

[0049] This embodiment prepares a composite manganese iron lithium phosphate material and a lithium ion battery with reference to the formula and method provided in Example 1. The difference from Example 1 is that when preparing the composite manganese iron lithium phosphate material, this embodiment adjusts the water content in the iron-containing solution so that the mass concentration of iron ions in the iron-containing solution is 10%. Except for the above differences, the operating steps for preparing the composite manganese iron lithium phosphate material and the lithium ion battery in this embodiment are strictly consistent with those in Example 1.

[0050] Comparative Example 1

[0051] This comparative example prepares a lithium-ion battery by referring to the formula and method provided in Example 1. The difference from Example 1 is that the positive electrode material used in this comparative example when preparing the positive electrode sheet is lithium iron manganese phosphate LiMn 0.5 Fe 0.5 .

[0052] Comparative Example 2

[0053] This comparative example refers to the formula and method provided in Example 1 to prepare a composite manganese iron lithium phosphate material and a lithium ion battery. The difference from Example 1 is that the composite manganese iron lithium phosphate material prepared in this comparative example does not introduce an iron-containing solution. In addition to the above differences, the operation steps for preparing the composite manganese iron lithium phosphate material and the lithium ion battery in this comparative example are strictly consistent with those in Example 1. Specifically, the method for preparing the composite manganese iron lithium phosphate material in this comparative example is:

[0054] S1. mixing a ferromanganese phosphate precursor with a lithium source, a carbon source, and a solvent to obtain a first slurry;

[0055] S2. The first slurry is then subjected to ball milling and fine grinding to obtain a second slurry having a particle size of 0.5 μm;

[0056] S4. After the second slurry is spray-dried, the obtained powder is calcined under the protection of an inert gas, wherein the reaction temperature of the calcination treatment is 600° C. and the reaction time is 5 hours to obtain a composite manganese iron lithium phosphate material.

[0057] Comparative Example 3

[0058] This comparative example refers to the formula and method provided in Example 1 to prepare a lithium-ion battery. The difference from Example 1 is that the molecular formula of the first metal material in the core of the composite manganese iron phosphate material prepared in this comparative example is LiMn x Fe (1-x) PO4, x≤0.3; the molecular formula of the second metal material of the first coating layer is LiMn y Fe (1-y) PO4, y=0.5. Except for the above differences, the operation steps for preparing the composite manganese iron phosphate lithium material and the lithium ion battery in this comparative example are strictly consistent with those in Example 1.

[0059] Test Case

[0060] 1. Test subjects

[0061] The composite lithium manganese iron phosphate materials and lithium ion batteries prepared in Examples 1 to 12 and Comparative Examples 1 to 3.

[0062] 2. Test Method

[0063] (1) Manganese dissolution: Weigh 2 portions of electrode materials of about 5g each as test objects and mark them. Dissolve the weighed test objects in 100mL of pure water, seal them, and let them stand for 70h. After filtering the test objects, dilute them in a 100mL volumetric flask, transfer 10mL of the test solution to a 100mL volumetric flask, dilute with pure water, and shake well. Determine the concentration of the filtered solution by inductively coupled plasma emission spectrometry and calculate the results.

[0064] (2) Cycle performance: The battery was charged and discharged at 25°C, 1C rate, and 2.2-4.3V. The cycle test was repeated for 500 cycles to obtain the cycle efficiency of the battery.

[0065] 3. Test results and analysis

[0066] The test results of this test example are shown in Table 2. Based on the data of Examples 1 to 10 and Comparative Examples 1 to 3, it can be seen that compared with pure lithium manganese iron phosphate, lithium manganese iron phosphate material coated only with carbon, and composite lithium manganese iron phosphate material with a higher manganese element content in the first coating layer than in the inner core layer, the composite lithium manganese iron phosphate material provided by the present invention can significantly improve its manganese dissolution problem.

[0067] It can be seen from the data of Examples 1 to 8 that the combination of organic iron and inorganic iron can effectively accelerate the ion exchange reaction, and the introduction of an organic carbon source can further significantly improve the manganese dissolution problem of lithium manganese iron phosphate, thereby improving its cycle performance.

[0068] It can be seen from the test data of Examples 1 and 9-10 that the iron ion concentration in the iron-containing solution will affect the manganese content in the second coating layer of the composite lithium manganese iron phosphate material, and further affect the manganese dissolution phenomenon of the lithium manganese iron phosphate.

[0069] Table 2. Test results of this test case

[0070] Group Cycle efficiency / % Mn dissolution / ppm Example 1 97 10 Example 2 99 22 Example 3 93 11 Example 4 98 14 Example 5 94 13 Example 6 99 22 Example 7 94 39 Example 8 95 19 Example 9 93 22 Example 10 96 39 Comparative Example 1 79 99 Comparative Example 2 82 95 Comparative Example 3 85 90

[0071] The above embodiments are only used to illustrate the technical solution of the present application rather than to limit the protection scope of the present application. Although the present application has been described in detail with reference to the preferred embodiments, a person skilled in the art should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.

Claims

1. A composite lithium manganese iron phosphate material, characterized in that: The composite lithium manganese iron phosphate material is arranged from the inside to the outside in sequence including a core, a first coating layer and a second coating layer; Wherein, the core comprises a first metal material, the molecular formula of the first metal material is LiMn x Fe (1-x) PO4, 0.4≤x≤0.6; The first coating layer includes a second metal material, the molecular formula of which is LiMn y Fe (1-y) PO4, 0≤y<0.01; The second coating layer includes a carbon material.

2. The composite lithium iron manganese phosphate material according to claim 1, characterized in that: The median particle size of the composite lithium manganese iron phosphate material is 6 to 10 μm, and the thickness of the first coating layer is 1 to 5 nm.

3. The composite lithium iron manganese phosphate material according to claim 1 or 2, characterized in that: The thickness of the second coating layer is 2-5 nm.

4. A method for preparing the composite lithium iron manganese phosphate material according to any one of claims 1 to 3, characterized in that: The steps include: S1. mixing a ferromanganese phosphate precursor with a lithium source, a carbon source, and a solvent to obtain a first slurry; S2. Then the first slurry is ground to obtain a second slurry; S3. mixing the second slurry with an iron-containing solvent and reacting at 20 to 80° C. for 2 to 12 hours to obtain a third slurry; S4. After the third slurry is dried, the obtained powder is calcined under the protection of an inert gas to obtain the composite lithium manganese iron phosphate material.

5. The method for preparing the composite lithium iron manganese phosphate material according to claim 4, characterized in that: The iron-containing solution includes at least one of a soluble organic iron salt and a soluble inorganic iron salt; Wherein, the soluble organic iron salt includes ferric acetate, ferric oxalate, and ferric ferrocyanide; The soluble inorganic iron salt includes at least one of ferric sulfate, ferrous sulfate, ferric chloride and ferrous nitrate.

6. The method for preparing the composite lithium iron manganese phosphate material according to claim 5, characterized in that: The iron-containing solution includes a soluble organic iron salt and a soluble inorganic iron salt. Calculated by mass ratio, the soluble organic iron salt: the soluble inorganic iron salt = 6-9: 1-4.

7. The method for preparing the composite lithium iron manganese phosphate material according to claim 4, characterized in that: In the iron-containing solution, the mass concentration of iron ions is 20-60%; and the added mass of the iron-containing solution is 0.5-10% of the ferromanganese phosphate precursor in the second slurry.

8. The method for preparing the composite lithium iron manganese phosphate material according to claim 4, characterized in that: In S1, calculated by mass ratio, the ferromanganese phosphate precursor: the lithium source: the carbon source = 1: 0.2-0.25: 0.03-0.

1.

9. The method according to claim 4, characterized in that: The particle size of the second slurry is 0.3-0.8 μm.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the composite lithium iron manganese phosphate material as claimed in any one of claims 1 to 3 or the composite lithium iron manganese phosphate material prepared by the method for preparing the composite lithium iron manganese phosphate material as claimed in any one of claims 4 to 9.